A finite set of equilibria for the indeterminacy of linear rational expectations models - Jean-Bernard Chatelain; Kirsten Ralf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper demonstrates the existence of a finite set of equilibria in the case of the indeterminacy of linear rational expectations models. The number of equilibria corresponds to the number of ways to select n eigenvectors among a larger set of eigenvectors related to stable eigenvalues. A finite set of equilibria is a substitute to continuous (uncountable) sets of sunspots equilibria, when the number of independent eigenvectors for each stable eigenvalue is equal to one.
Keywords: C60; C61; C62; E13; E60; 330; linear rational expectations models; sunspots; indeterminacy; multiple equilibria; matrix Riccati equation